Fungal contamination and azole-resistance in tea and other medicinal plants commercially available in Portugal - Simões, A. (2021)
IPL/2020/TEAResMyc_ESTeSL. Project "Resistant mycobiota and mycotoxigenic profile of tea and medicinal plants”.